About the permanence of Darwin in Perú (1835). An advance of a research - Arana Bustamante, Luis (2017)
This is the comunication of the preliminary findings of a research about the permanence of Charles Darwin in Perú. Making use of the now disposables pertinent sources about the naturalist published by Internet proyects, I try to offer an analysis of impressions and activities of Charles Darwin during his limited permanence in our country.